Japan’s Multicultural Diplomacy through JENESYS 2024: Cultural Exchange and Soft Power toward Indonesian Youth - Muhammad Imran Nur; Sakinah Fitrah Rahmah; Muhammad Arjalulwahid Aliyah; Muhammad Dhiemas Anggareksa; Lady Nubailah Wahdah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This research analyzes multicultural practices within Japan’s social context, both domestically and in international relations. The study focuses on how Japanese society facilitates the development of multicultural identities, particularly through interactions between Japanese citizens, immigrant populations, and ethnic minority communities. In the context of globalization, Japan has increasingly positioned multicultural engagement as an important strategy for strengthening social cohesion and international cooperation. Through the JENESYS 2024 program, a cultural exchange initiative involving youth from East Asia, Japan seeks to channel the values of multiculturalism into tangible benefits, including the enhancement of strategic partnerships with Southeast Asian countries such as Indonesia and the reinforcement of cultural diplomacy to maintain its role as a regional power in Asia. Based on the author’s observations, JENESYS 2024 includes at least three main components: the introduction of collective memory, immersive cultural experiences, and direct multicultural interactions among participants. These activities provide participants with opportunities to understand cultural diversity while building mutual understanding between nations. This paper further highlights how Japan develops cultural communication with Indonesia, the world’s largest Muslim-majority country, and demonstrates how Japan’s soft diplomacy through JENESYS contributes to strengthening its international image. Ultimately, the program reinforces Japan’s position as a cultural and civilizational reference point among Indonesian youth while promoting long-term intercultural collaboration.